Odnos do demence in stigma demence - Ošlak, Katja (Javno zdravje, 2017)
The purpose of the study was to explore attitudes towards dementia and consequent manifestation and intensity of stigma concerning people with dementia. In the study, we used the adaptation of a questionnaire that was developed for the purpose of the Alzheimer's Australia 2012 project. It measures two components of stigma (personal avoidance and person centredness). We added two scales that measure the possibility of not seeking help and delaying seeking help in case of noticing the early signs of dementia. Study included 153 participants, aged between 19 and 87 years. The results showed some statistically significant differences in experiencing stigma considering some social-demographic factors. Men had higher level of personal avoidance and lower level of person centredness than women. Participants with lower education had higher levels of personal avoidance, but concerning level of education, we did not find any differences in experiencing person centredness. Contrary to the expectations was also the fact that older participants did not show higher levels of person centredness. It was found that intensity of person centredness at first ascends with age, but later starts descending. Opposite effect was found with personal avoidance, which was strongest with youngest and eldest participants. It was confirmed that people that had already had some contact with dementia patients in the past showed lower level of personal avoidance. It was also found out that experiencing negative views and desire for avoidance of dementia patients positively correlates with not seeking help and delaying seeking help in hypothetical case of experiencing early signs of dementia.
Keywords: bolniki; demenca; dementia; iskanje pomoči; izogibanje; patients; person centeredness; personal avoidance; seeking help; sprejemanje; stigmatizacija; stigmatization